Countering the Education Bog for the Girl-Child: Global Progress to Build on the Ugandan Case - Luwemba, Musa Maswanku; Aiseta, Aisha (Islamic University Journal of Social Sciences, 2021)
One of the primary rights that is required for progress is education. A county that invests in both the girl and boy child's education is one that is committed to long-term, dependable, and sustainable growth. In Africa, however, boys have a considerably better probability of getting enrolled, admitted, retained, and completing their education than girls. This is owing to educational stumbling blocks and cultural, economic, political, and social problems. These have a lengthy history, yet they are still relevant today. The question now is how long these obstacles will persist, and if so, how they might be overcome in order to attain the gender equality enshrined in Uganda's constitution, as well as many other international agreements.
Keywords: Education bog, girl-child, global progress, Uganda, countering